Simulation and Analysis of Integral LQR Controller for Inner Control Loop Design of a Fixed Wing Micro Aerial Vehicle (MAV). (2016) - Anjali, B.S.; Vivek, A.; Nandagopal, J.L.
Abstract: The focus of this paper is on the autopilot control loop design of fixed wing Micro Aerial Vehicles (MAVs).The control methodologies used to design the lateral and longitudinal control are based on Proportional Integral Derivative (PID) and Linear Quadratic Regulator (LQR) with integral action control techniques. The design of these controllers is based on the assumption that the system dynamics can be decoupled to longitudinal and lateral dynamics. A nominal model is chosen among many linear models linearized under various operating conditions. The resulting controllers are simulated in MATLAB® SIMULINK® workspace and results are studied. The simulation results show that both the controllers gives satisfactory performances with or without disturbances, but the LQR controller provides better disturbance rejection and exhibits better overall performance.